Linear IgA bullous dermatosis–a fifty year experience of Warsaw Center of bullous diseases - Kowalewski, Cezary; Wozniak, Katarzyna (Frontiers in Immunology, 2025)
Linear IgA bullous dermatosis (LABD) is a rare subepidermal blistering disorder characterized by the presence of linear IgA deposits at the basement membrane zone (BMZ) by direct immunofluorescence (DIF). This entity was first described by Chorzelski and Jablonska from Warsaw Center of Bullous Diseases, Poland. The disease affects children and adults, whereby they differ in terms of clinical picture and course. Among polish patients with LABD mucous membrane involvement was exceptional, although, we reported a case presenting severe scarring of esophagus and conjunctivae with circulating IgG and IgA antibodies to LAD-1 antigen. Severe mucosal involvement was also observed in IgA-epidermolysis bullosa acquisita (EBA). Immunologically, LABD is characterized by circulating IgA antibodies directed to several epitopes of antigen BP180: LAD-1, 97kD, NC16A. Other BMZ antigens, like BP230, laminin 332, type VII collagen or p200 may be affected. We as a first published a case of anti-p200kD pemphigoid mediated by IgA. Our immunoelectron microscopic studies showed that the epitopes recognized by LABD sera are ultrastructurally localized in the lamina lucida. The antigenic heterogeneity, low titer of IgA antibodies and the lack of commercially available tests for some antigens (LAD-1, p200kD) makes the diagnosis challenging in many cases. It is under debate whether these cases are the subtypes of LABD or they represent a separate entities (IgA-p200 pemphigoid, IgA-MMP or IgA-EBA). Since, they differ in terms of clinical course, mucosal involvement, coexisting disorders, response to the treatment and prognosis, their differentiation is mandatory. In the literature there are many cases with undetectable circulating IgA antibodies in whom LABD was recognized based on DIF only. To avoid misdiagnosis, more sophisticated methods should be used, like direct immunoeletron microscopy (IEM), which is a time-consuming technique. The alternative for IEM may be: a) analysis of the BMZ serration pattern, b) immunofluorescence mapping of blister, c) direct salt split (patient’s) skin, d) fluorescence overlay antigen mapping by laser scanning confocal microscopy. The two latter methods were established by the authors years ago and they allowed precise diagnosis (i.e., differentiation LABD from IgA-EBA), initiation of proper therapy and assessment of prognosis in many cases mediated by IgA.